The Concept Of Human Creation According To Islamic Scholars As A Criticism Of Homo Economicus - Umam, Khairul; Yazidurrahma, Akbar (Mahad Aly Al Fithrah, 2024)
Humans who were created with a lot of diversity and abilities and strengths that are more than other living things make them superior in many aspects. But unfortunately, it turns out that this diversity has resulted in the birth of a distorted perspective on world life, especially regarding wealth. Not a few people or individuals judge other humans by the parameters of the assets they have and ignore other aspects of being human. This principle is the root of the world view of Homo Economicus. This study aims to criticize and refute the ideas and perspectives of Homo Economicus on human essence through the ideas of Muslim scholars about human nature. This research is a conceptual review of the literature using a normative descriptive method. The results of the study show that the emergence of Homo Economicus is caused because they adhere to the principle that views life only based on rationality and reason, whereas according to Islam this is not sufficient to be relied upon as the basis for the absolute truth of knowledge, because humans are entities that are manifested from the combination of body and spirit. , the second is what represents reason and al-nafsu